Synthesis and Properties of Tin Sulfide Thin Films from Nanocolloids Prepared by Pulsed Laser Ablation in Liquid. Issue 9 (3rd January 2017) - Johny, Jacob; Sepulveda‐Guzman, Selene; Krishnan, Bindu; Avellaneda, David A.; Aguilar Martinez, Josue A.; Shaji, Sadasivan
Abstract: Tin sulfide (SnS) nanoparticles were synthesized by pulsed laser ablation in liquid (PLAL) technique using an Nd:YAG laser operated at 532 nm. SnS thin films were deposited by spraying the colloidal suspension onto the heated substrates. The influence of different liquid media (dimethyl formamide and isopropyl alcohol) on the thin film properties were studied. Morphology, crystalline structure, and chemical composition of the nanoparticles were identified using transmission electron microscopy with energy dispersive X‐ray analysis. The crystalline structure of the thin films was analyzed by using grazing incidence X‐ray diffraction, and the chemical states by X‐ray photoelectron spectroscopy. Scanning electron microscopy was employed for the morphological analysis of the thin films. Annealing the films at 380 °C improved the crystallinity of the films exhibiting a layered morphology, which may be useful in optoelectronic and sensing applications. Cyclic voltammetry studies showed that the films have good electrochemical properties. Abstract : Nanostructured SnS thin films were synthesized combining PLAL with spray technique. Layer‐like morphology was obtained for the films (see Figure). Electrochemical and opto‐electronic properties of the films were investigated in addition to the characterization of SnS thin films as well as nanoparticles.